A composite electrolyte membrane, a preparation method thereof and application thereof in a full-solid lithium metal battery

CN122899010APending Publication Date: 2026-10-13SUZHOU NENGYU TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611071805.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但传统的聚环氧乙烷(PEO)基固态聚合物电解质存在三大核心缺陷:一是室温离子电导率低,通常仅为10-5~10-4S/cm,无法满足高倍率充放电需求;二是锂迁移数低(通常<0.2),导致严重的浓差极化;三是电化学稳定性窗口窄(<4.5V),无法匹配钴酸锂、镍钴锰酸锂等高电压正极材料

Benefits of technology

[0071]与现有技术相比,本发明具有以下显著的有益效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899010A_ABST
    Figure CN122899010A_ABST
Patent Text Reader

Abstract

The application provides a composite electrolyte membrane, a preparation method thereof and application thereof in a full solid-state lithium metal battery. The preparation of the composite electrolyte membrane comprises the following steps: mixing a polymer matrix, a crosslinking agent and an organic cage ion conductor, stirring in a mixed solvent until a transparent solution is formed, adding lithium salt and an initiator, and continuously stirring to obtain a uniform transparent spinning precursor solution; performing high-speed electrospinning on the spinning precursor solution to collect a precursor fiber membrane; and solidifying the precursor fiber membrane to make the crosslinking agent undergo a polymerization reaction, form a crosslinked three-dimensional nanofiber network structure, and obtain the composite electrolyte membrane. Through the synergistic effect of the organic cage ion conductor and the three-dimensional crosslinked network of electrospinning, the perfect unity of high ionic conductivity, high lithium transference number, a wide electrochemical window, an ultrathin thickness and high mechanical strength is realized, and the industry problem that the performance of a solid-state polymer electrolyte is difficult to consider is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state lithium battery technology, and relates to a composite electrolyte membrane, its preparation method and application, especially to a method for preparing an organic cage-reinforced electrospun composite electrolyte membrane and its application in all-solid-state lithium metal batteries. It is particularly suitable for solving the core technical problems of low room temperature ionic conductivity, low lithium transference number, narrow electrochemical window, insufficient mechanical strength and lithium dendrite growth in solid polymer electrolytes. Background Technology

[0002] With the rapid development of electric vehicles and portable electronic devices, the market has placed higher demands on the energy density and safety of lithium-ion batteries. Lithium metal anodes, with their ultra-high theoretical specific capacity of 3860 mAh / g and extremely low electrochemical potential, have become a core technology direction for next-generation high-energy-density batteries. However, the growth of lithium dendrites can lead to battery short circuits, severely restricting the safe application of lithium metal batteries. Furthermore, traditional liquid electrolytes are prone to decomposition under high voltage, making them unsuitable for high-voltage cathode materials.

[0003] Solid polymer electrolytes, with their excellent flexibility, processing performance, and interfacial compatibility, have become a key solution to the aforementioned problems. However, traditional polyethylene oxide (PEO)-based solid polymer electrolytes have three major drawbacks: firstly, their room temperature ionic conductivity is low, typically only 10 Ω·cm. -5 ~10 -4 The first problem is that the S / cm ratio cannot meet the requirements of high-rate charge and discharge; the second is that the lithium transference number is low (usually <0.2), which leads to severe concentration polarization; and the third is that the electrochemical stability window is narrow (<4.5V), which cannot match high-voltage cathode materials such as lithium cobalt oxide and lithium nickel cobalt manganese oxide.

[0004] In recent years, porous organic cages, as a novel type of porous material, have attracted widespread attention due to their discrete molecular structure and excellent solution processability. Studies have shown that organic cage-based lithium-ion conductors, such as lithium-cage-based lithium perchlorate, exhibit a high room-temperature ionic conductivity of 5.13 × 10⁻⁶. -5 With excellent properties such as S / cm, lithium transference number of approximately 0.7, and a wide electrochemical window of up to 5.0V, and being soluble in various polar solvents, it can be fabricated into electrodes using traditional slurry coating methods. However, the mechanical strength of standalone organic cage electrolytes is insufficient to form a self-supporting ultrathin electrolyte membrane, making it difficult to effectively suppress lithium dendrite growth. Traditional electrospinning technology typically uses the fiber membrane only as a mechanical support framework, requiring the casting of highly conductive liquid electrolyte within the framework. This process is not only complex but also poses a safety hazard due to liquid electrolyte leakage.

[0005] Existing technologies have many fatal flaws in the actual industrialization process:

[0006] Defect 1: Low room-temperature ionic conductivity, failing to meet the requirements of high-rate charge and discharge. The room-temperature ionic conductivity of traditional PEO-based solid polymer electrolytes is typically only 10. -6 ~10 -5 Even after modification with ceramic fillers, the S / cm ratio is difficult to exceed 10. -4 The conductivity is on the order of S / cm. Low ionic conductivity leads to severe polarization and high heat generation during high-rate charge / discharge, resulting in low energy efficiency and safety hazards. According to industry test data, lithium metal batteries using traditional PEO-based electrolytes typically retain less than 70% of their capacity at 1C discharge rate, failing to meet the fast-charging requirements of power batteries. Even with the latest composite electrolyte technologies, room temperature conductivity is generally around 5 × 10⁻⁶. -5 S / cm or less, 10 meters away from practical application -4 There is still a significant gap in the S / cm threshold.

[0007] Defect 2: Low lithium transference number, severe concentration polarization, and poor rate performance. Traditional polymer electrolytes typically have a lithium transference number below 0.2, meaning that under an electric field, most of the current is carried by anions, with lithium ion migration contributing very little. This low lithium transference number leads to severe concentration polarization during charging and discharging, forming a large concentration gradient on the electrode surface. This not only limits the battery's rate performance but also exacerbates the uneven growth of lithium dendrites. Studies have shown that increasing the lithium transference number from 0.2 to 0.6 can increase the battery's critical current density by more than three times, and significantly reduces the tendency for lithium dendrite growth. However, current technologies struggle to increase the lithium transference number above 0.5 through simple filler doping, often at the expense of ionic conductivity.

[0008] Defect 3: Narrow electrochemical stability window, unable to match high-voltage cathodes. The electrochemical oxidation stability of traditional PEO-based electrolytes is typically below 4.5V, and significant oxidative decomposition occurs above 4.3V, making them unsuitable for cathode materials operating at 4.4V, 4.5V, or even higher voltages. In pursuit of higher energy density, the operating voltage of power battery cathode materials is continuously increasing, evolving from traditional 3.7V-level LFP and 4.2V-level NCM to 4.4V and 4.5V high-voltage NCM and LCO. The voltage stability of the electrolyte has become a key bottleneck restricting the improvement of battery energy density. Although fluorination modification can improve the oxidative stability of polymers to some extent, it often leads to a decrease in ionic conductivity and a significant increase in material costs, resulting in poor cost-effectiveness.

[0009] Defect 4: Insufficient mechanical strength, making it difficult to effectively suppress lithium dendrite growth. Pure polymer electrolytes typically have low mechanical strength, with tensile strength mostly below 5 MPa, making it difficult to withstand the stress generated by lithium dendrite growth and effectively prevent battery short circuits caused by lithium dendrite punctures. Although electrospinning and cross-linking can improve the mechanical strength of the electrolyte membrane to some extent, this often sacrifices ion conductivity, leading to a dilemma of "high strength equals low conductivity, and high conductivity equals low strength." An ideal solid-state electrolyte needs to possess both high ion conductivity and high mechanical strength, but current technology struggles to achieve a perfect balance between the two. According to mechanical simulations, to completely suppress lithium dendrite growth, the shear modulus of the electrolyte needs to be more than twice that of lithium metal (approximately 6 GPa), a task virtually impossible for polymer electrolytes.

[0010] Defect 5: Excessive membrane thickness leads to significant energy density loss. Polymer electrolyte membranes prepared using traditional solution casting methods are typically 50-100 μm thick, or even thicker. Excessive thickness not only increases the battery's internal resistance but also significantly reduces its overall energy density. With the trend towards thinner profiles and higher energy density, the thickness of the electrolyte membrane has become a crucial optimization target. Ideally, the thickness of a solid-state electrolyte membrane should be controlled below 20 μm to compete with traditional liquid electrolyte membrane systems in terms of volume and weight. However, current technologies struggle to reduce the membrane thickness to below 30 μm while maintaining mechanical strength and ion conductivity; the fabrication technology of ultrathin electrolyte membranes remains a challenge for the industry.

[0011] Defect 6: Poor interface stability and short cycle life. The interface stability between the polymer electrolyte and the lithium metal anode is a key factor affecting battery cycle life. Traditional PEO-based electrolytes are highly reactive with lithium metal, leading to continuous side reactions that cause a continuous increase in interface impedance and rapid capacity decay. Simultaneously, the volume changes of lithium metal during deposition / stripping deteriorate the interface contact, further exacerbating performance degradation. Although interface stability can be improved to some extent through interface coatings and additives, the effects are limited and increase process complexity and cost. Constructing a stable lithium metal interface to achieve long cycle life is one of the core challenges for the industrialization of solid-state lithium metal batteries.

[0012] Current mainstream technologies include: CATL (CN122246216A): sulfide + polymer composite system; BYD (CN121862833A): modified vinylide-fluoride polymer electrolyte; Samsung SDI (CN111146492B): sulfide all-solid-state stacked structure; and domestic research institutions (CN116864801B): electrospinning core-shell structure composite electrolyte. None of these approaches have achieved the organic integration of organic cage ion conductors with electrospinning in-situ photopolymerization technology.

[0013] Therefore, there is an urgent need in this field to develop a novel solid polymer electrolyte that can simultaneously achieve high ionic conductivity, high lithium transference number, wide electrochemical window, ultrathin thickness, and high mechanical strength. Specifically, this would be an organic cage-reinforced electrospun composite electrolyte membrane, to address the shortcomings of traditional solid polymer electrolytes, such as low room temperature ionic conductivity, low lithium transference number, narrow electrochemical window, insufficient mechanical strength, excessive film thickness, and poor interface stability, which prevent the simultaneous achievement of multiple objectives including high ionic conductivity, high lithium transference number, wide electrochemical window, ultrathin thickness, and high mechanical strength. Summary of the Invention

[0014] Based on the deficiencies of existing technologies, the first objective of this invention is to provide a method for preparing an organic cage-reinforced electrospun composite electrolyte membrane; the second objective is to provide the organic cage-reinforced electrospun composite electrolyte membrane prepared by this method; the fourth objective is to provide an application of the organic cage-reinforced electrospun composite electrolyte membrane in the preparation of all-solid-state lithium metal batteries; and the fifth objective is to provide an all-solid-state lithium metal battery comprising the above-mentioned composite electrolyte membrane. This invention achieves a perfect balance of high ionic conductivity, high lithium transport number, wide electrochemical window, ultra-thin thickness, and high mechanical strength through the synergistic effect of the organic cage ion conductor and the three-dimensional cross-linked network of electrospinning, thus completely solving the industry problem of the difficulty in achieving a balance between the performance of solid polymer electrolytes.

[0015] The objective of this invention is achieved through the following technical solution:

[0016] On one hand, the present invention provides a method for preparing an organic cage-reinforced electrospun composite electrolyte membrane, characterized in that the preparation method includes the following steps:

[0017] Step 1: Mix the polymer matrix, crosslinking agent and organic cage ionic conductor, add to the mixed solvent and stir until a transparent solution is formed, then add lithium salt and initiator, and continue stirring to obtain a uniform and transparent spinning precursor solution;

[0018] Step 2: The spinning precursor solution is subjected to high-speed electrospinning to collect the precursor fiber membrane.

[0019] Step 3: The precursor fiber membrane is cured to allow the crosslinking agent to polymerize and form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

[0020] In this invention, the organic cage ion conductor is uniformly dispersed in nanofibers, serving as an ion conduction enhancer to provide high ion conductivity and high lithium transference number; the polymer matrix and crosslinking agent form a crosslinked network through in-situ photocuring, providing excellent mechanical strength and dimensional stability; the lithium salt provides migratable lithium ions, ensuring the ion conduction capability of the electrolyte.

[0021] In the above method, preferably, in step one, the polymer matrix is ​​selected from one or more combinations of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyethylene oxide (PEO); but is not limited thereto.

[0022] In the above method, preferably, in step one, the polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) with a molecular weight Mn = 400,000. PVDF-HFP exhibits excellent film-forming properties, mechanical strength, and electrochemical stability. Its hexafluoropropylene component disrupts the crystallinity of PVDF, increasing the proportion of amorphous regions and facilitating ion conduction. Simultaneously, the fluorinated structure of PVDF-HFP endows it with excellent high voltage stability and flame retardant properties.

[0023] In this invention, the organic cage itself has a wide electrochemical window of 5.0V, and its molecular structure does not contain easily oxidized ether bonds, resulting in excellent high-voltage stability. The fluorinated structure of the PVDF-HFP matrix also exhibits excellent antioxidant properties. Together, these two components further broaden the electrochemical window of the composite electrolyte to 5.6V. Simultaneously, the in-situ cross-linked three-dimensional network structure reduces the migration of low-molecular-weight components, preventing the oxidative decomposition of oligomers under high voltage, and further improving electrochemical stability.

[0024] Furthermore, the fluorinated structure of the PVDF-HFP matrix endows it with excellent flame retardant properties, forming a dense char layer during combustion to prevent the transfer of heat and oxygen; the organic cage and cross-linked network are also flame-retardant materials. The three-dimensional cross-linked network structure gives the electrolyte membrane good mechanical flexibility and puncture resistance, preventing leakage and combustion even when subjected to mechanical damage.

[0025] In the above method, preferably, in step one, the crosslinking agent is selected from one or more combinations of polyethylene glycol diacrylate (PEGDA), trimethylolpropane triacrylate (TMPTA), ethoxylated trimethylolpropane triacrylate (EO-TMPTA), and pentaerythritol tetraacrylate (PETA); but is not limited thereto.

[0026] In the above method, preferably, in step one, the crosslinking agent is polyethylene glycol diacrylate (PEGDA) with a molecular weight Mn = 1000 g / mol. The acrylate groups at both ends of PEGDA can undergo free radical polymerization under ultraviolet light initiation to form a crosslinked three-dimensional network structure, which significantly improves the mechanical strength and dimensional stability of the electrolyte membrane. Simultaneously, the polyethylene glycol segments of PEGDA have good lithium-ion solvation ability, which can promote ion conduction.

[0027] In the above method, preferably, in step one, the organic cage ion conductor is selected from one or more combinations of lithium-cage-based ion conductors—lithium perchlorate, imine cages, borate ester cages, and covalent organic framework (COF) molecular cages; but is not limited thereto.

[0028] In the above method, preferably, in step one, the organic cage ion conductor is a lithium-cage-based ion conductor—lithium perchlorate—which is used after being vacuum dried at 80°C for 12 hours. The organic cage ion conductor has a discrete molecular structure and excellent solution processability; it is soluble in various polar solvents such as N,N-dimethylformamide and acetone, and can achieve molecular-level homogeneous mixing with the polymer matrix. Its cationic framework can anchor anions, significantly increasing the lithium transference number; simultaneously, it has a wide electrochemical window of up to 5.0V, making it compatible with high-voltage cathode materials.

[0029] In the above method, preferably, the lithium-cage-based ion conductor-lithium perchlorate is a conventional method in the art, or is prepared according to the following method (reaction process as follows) Figure 3 (as shown)

[0030] Step 1: Synthesis of imine cage (CC1)

[0031] Weigh equimolar amounts of 1,3,5-tricarboxymethyl phloroglucinol and ethylenediamine, dissolve them in an anhydrous solvent (such as methanol, acetonitrile, or a chloroform / methanol mixture), and stir the mixture at room temperature for 24–72 h under an inert gas atmosphere (such as nitrogen or argon). The precipitate formed by the reaction is collected by filtration, washed with a cold solvent (such as methanol, acetonitrile, or a chloroform / methanol mixture) to remove unreacted monomers, and dried to obtain the intermediate imine cage CC1.

[0032] Step 2: Preparation of amine cage (RCC1) by reduction

[0033] The dried CCC1 was suspended in tetrahydrofuran or methanol; excess sodium borohydride was added in batches under ice bath cooling; after the addition was complete, the mixture was brought back to room temperature and stirred for 12-24 h until the imine bonds were completely reduced to amine bonds; after the reaction was completed, excess sodium borohydride was carefully quenched with water; the organic solvent was removed by rotary evaporation, and the remaining solid was washed with water several times to remove inorganic salts. After vacuum drying, a white powdery reduced amine cage RCC1 was obtained.

[0034] Step 3: Protonation to prepare chloride salt (RCC1-Cl)

[0035] RCC1 is dispersed in a dilute hydrochloric acid solution or by passing hydrogen chloride gas into its alcoholic solution. The nitrogen atom on the amine cage captures a proton to form an ammonium cation, while simultaneously binding a chloride ion as a counter anion. After the reaction is complete, the solid product is collected by evaporating the solvent or by precipitation, and washed with ethanol or ether to obtain the protonated chloride precursor RCC1-Cl.

[0036] Step 4: Preparation of the final product (RCC1-LiClO4) using lithium salt composites.

[0037] RCC1-Cl was dispersed in a 15wt% lithium perchlorate-ethyl acetate solution and subjected to ion exchange at 50°C. The solution was changed every 48 hours for a total of 3 times. Centrifugation was used to separate the porous organic cage molecular framework and the compound formed by the combination of perchlorate ions. After washing, the compound was mixed with lithium perchlorate in an ethanol-water solvent. After removing the solvent, the compound was dried under vacuum at 80°C overnight to obtain the organic cage-based lithium-ion conductor lithium-cage-based ion conductor lithium perchlorate.

[0038] In this invention, the organic cage ion conductor itself possesses excellent ion conductivity. Its discrete molecular structure and porous characteristics provide a rapid transport channel for lithium ions. Simultaneously, the cationic framework of the organic cage can effectively anchor anions, restricting their migration and thus significantly increasing the lithium transference number. The organic cage is soluble in polar solvents, enabling molecular-level homogeneous mixing with the polymer matrix, avoiding the agglomeration problem of traditional ceramic fillers, and resulting in a more continuous and smooth ion transport path. The amorphous region of PVDF-HFP and the polyethylene glycol segments of PEGDA also provide additional transport paths for lithium ions, forming a synergistic effect with the ion conduction of the organic cage.

[0039] Furthermore, the positively charged cationic framework of the organic cage can electrostatically interact with electrons on the lithium metal surface, forming a uniform adsorption layer that guides uniform lithium ion deposition and inhibits the uneven growth of lithium dendrites. The SEI film induced by the organic cage is rich in inorganic lithium salt components, exhibiting high ionic conductivity and high mechanical strength, enabling it to exist stably and effectively block lithium dendrite growth. The high specific surface area of ​​the three-dimensional nanofiber network also increases the contact area between the electrolyte and the electrode, reducing interfacial impedance.

[0040] In the above method, preferably, in step one, the mass ratio of the polymer matrix, the crosslinking agent, and the organic cage ion conductor is (5~7):(2~3):(1~2). Within this ratio range, sufficient mechanical strength can be guaranteed while achieving excellent ion conduction performance.

[0041] In the above method, more preferably, in step one, the mass ratio of the polymer matrix, the crosslinking agent and the organic cage ion conductor is (5.5~6.5):(2~2.5):1.5.

[0042] More preferably, in step one, the mass ratio of the polymer matrix, the crosslinking agent, and the organic cage ion conductor is 6:2.5:1.5.

[0043] In the above method, preferably, in step one, the mixed solvent is a mixture of N,N-dimethylformamide and acetone in a volume ratio of 1:1.

[0044] In the above method, preferably, in step one, after adding the mixed solvent, the mixture is stirred at room temperature for 6 hours.

[0045] In the above method, preferably, in step one, the lithium salt is selected from one or more combinations of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4); but is not limited thereto.

[0046] In the above method, preferably, in step one, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which is used after being vacuum dried at 100°C for 12 hours. LiTFSI has high dissociation degree, high ionic conductivity and excellent electrochemical stability.

[0047] In the above method, preferably, in step one, the amount of lithium salt added is 18wt% to 22wt% of the total mass of the polymer matrix, crosslinking agent and organic cage ion conductor.

[0048] More preferably, in step one, the amount of lithium salt added is 20 wt% of the total mass of the polymer matrix, crosslinking agent and organic cage ion conductor.

[0049] In the above method, preferably, in step one, the initiator is selected from photoinitiators or thermal initiators, depending on the curing method in step three.

[0050] In the above method, preferably, the photoinitiator is selected from phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; but it is not limited thereto.

[0051] In the above method, preferably, the thermal initiator is selected from azobisisobutyronitrile; but it is not limited thereto.

[0052] In the above method, preferably, the amount of initiator added is 0.5% of the total mass of the polymer matrix, crosslinking agent and organic cage ionic conductor.

[0053] In the above method, preferably, in step two, the parameters of the high-speed electrospinning are: injection flow rate 0.8~1.2mL / h, spinning positive voltage 15~20kV, negative voltage -2~-4kV, and collecting roller speed 2500~3500rpm.

[0054] More preferably, in step two, the parameters of the high-speed electrospinning are: injection flow rate 1 mL / h, spinning positive voltage 17 kV, negative voltage -3 kV, and collecting roller speed 3000 rpm.

[0055] The nanofibers prepared by electrospinning in this invention possess high specific surface area and aspect ratio, with the fibers overlapping to form a continuous network structure. In-situ photocuring induces a cross-linking reaction in PEGDA, forming chemically bonded cross-linking points within and between the fibers, further enhancing the mechanical strength of the network structure. This three-dimensional cross-linked network not only exhibits high tensile strength but also good flexibility, enabling it to adapt to volume changes during lithium metal deposition / stripping and maintain interfacial contact stability.

[0056] In the above method, preferably, in step three, the curing is selected from photocuring or thermocuring.

[0057] In the above method, preferably, the photocuring conditions are: curing is performed by irradiation with a 30W, 365nm wavelength ultraviolet light, and the curing time is 4~6 minutes, preferably 5 minutes.

[0058] In the above method, preferably, the heat curing conditions are: heating and curing at 60~80℃ for 2~4 hours.

[0059] In this invention, electrospinning technology has been industrialized, with mature equipment and continuous production capabilities. In-situ UV curing is fast, requiring only 5 minutes to complete curing, resulting in high production efficiency. The entire preparation process has controllable parameters, good batch consistency, and stable product quality. Compared to traditional thermosetting processes, UV curing offers significant cost and environmental advantages due to its low energy consumption, high speed, and lack of solvent residue.

[0060] On the other hand, the present invention also provides an organic cage-reinforced electrospun composite electrolyte membrane, which is prepared by the above-described method.

[0061] In the aforementioned organic cage-reinforced electrospun composite electrolyte membrane, preferably, the composite electrolyte membrane has a three-dimensional cross-linked nanofiber network structure; its thickness is 12~20μm, preferably 15~18μm; its tensile strength reaches 9.8MPa~14.2MPa; and its room temperature ionic conductivity is 1.8×10⁻⁶. -4 S / cm ~ 3.2 × 10 -4S / cm; lithium transference number is 0.58~0.7; electrochemical window is 5.4V~5.7V.

[0062] In this invention, electrospinning technology can directly prepare ultrathin self-supporting fiber membranes, and the membrane thickness can be precisely controlled by adjusting the spinning time. The three-dimensional cross-linked network structure ensures that the ultrathin film still has sufficient mechanical strength and will not break or short-circuit due to its thinness. The 12~20μm ultrathin electrolyte membrane is comparable to the traditional liquid electrolyte membrane system in terms of volume and weight, solving the problem of energy density loss caused by the large thickness of solid electrolytes.

[0063] Furthermore, the present invention also provides the application of the above-mentioned organic cage-reinforced electrospun composite electrolyte membrane in the preparation of all-solid-state lithium metal batteries.

[0064] In another aspect, the present invention also provides an all-solid-state lithium metal battery, wherein the electrolyte membrane used in preparing the all-solid-state lithium metal battery is the above-mentioned organic cage reinforced electrospun composite electrolyte membrane.

[0065] The process for preparing an all-solid-state lithium metal battery using the aforementioned composite electrolyte membrane is as follows:

[0066] A. Preparation of positive electrode sheet: A positive electrode sheet is prepared by mixing positive electrode active material, conductive agent and binder in a mass ratio of 92:4:4, with an areal density of 25~35mg / cm²; the positive electrode active material includes one or more of lithium iron phosphate, lithium cobalt oxide and lithium nickel cobalt manganese oxide;

[0067] B. Battery assembly: Using lithium metal foil as the negative electrode, the above-mentioned composite electrolyte membrane is placed between the positive and negative electrodes and stacked to form an all-solid-state lithium metal battery;

[0068] C. Battery activation: Formation activation is performed at 45°C with a small current of 0.1C to ensure full contact between the electrolyte and the electrode interface and form a stable interface layer;

[0069] D. Cyclic operation: It can perform charge and discharge cycles within a temperature range of 25~60℃, and the operating voltage can reach above 4.4V, achieving high energy density and long cycle life.

[0070] The beneficial effects of this invention are:

[0071] Compared with the prior art, the present invention has the following significant advantages:

[0072] (1) The composite electrolyte membrane constructed in this invention is a three-dimensional cross-linked nanofiber network structure, which significantly improves mechanical strength and effectively inhibits lithium dendrite growth. Combining the high specific surface area advantage of electrospinning and the cross-linking characteristics of in-situ photocuring, this invention constructs a three-dimensional cross-linked nanofiber network structure. The tensile strength of the electrolyte membrane reaches more than 12.5 MPa, which is 2 to 3 times that of traditional PEO-based electrolytes. The high-strength three-dimensional network structure can effectively withstand the stress generated by lithium dendrite growth, prevent lithium dendrite puncture, and significantly improve battery safety. The lithium symmetric battery prepared using this composite electrolyte membrane can stably cycle for more than 5000 hours at a current density of 0.1 mA / cm², which is more than 5 times that of the prior art.

[0073] (2) The composite electrolyte membrane of the present invention has the effects of enhanced organic cage ion conductor, significantly improved ion conductivity and lithium transference number. In the preparation method of the present invention, by introducing an organic cage ion conductor as an ion conduction enhancer, the room temperature ion conductivity of the composite electrolyte reaches 10. -4 The S / cm ratio is on the order of magnitude, which is 1 to 2 orders of magnitude higher than that of traditional PEO-based electrolytes; the lithium transference number reaches 0.6 to 0.7, which is more than 3 times that of traditional polymer electrolytes. The high ionic conductivity and high lithium transference number significantly reduce battery polarization and greatly improve the battery's rate performance and energy efficiency.

[0074] (3) The composite electrolyte membrane of the present invention possesses excellent high voltage stability, can be matched with high-voltage cathodes, and significantly improves energy density. The electrochemical oxidation window of the composite electrolyte of the present invention reaches 5.6V, which is much higher than the 4.5V of the traditional PEO-based electrolyte, and can be matched with 4.5V high-voltage lithium cobalt oxide and lithium nickel cobalt manganese oxide cathode materials. High voltage stability enables the battery to operate at higher voltages, significantly improving the battery's energy density.

[0075] (4) The composite electrolyte membrane of the present invention adopts an ultra-thin thickness design, which can effectively improve the overall energy density of the battery. The thickness of the electrolyte membrane prepared by the present invention can be controlled at 12~20μm, which is much lower than the 100μm of the traditional solution casting method, and also thinner than most electrospun composite electrolyte membranes. The ultra-thin thickness design effectively reduces the volume and mass ratio of the electrolyte, thereby improving the overall energy density of the battery.

[0076] (5) The composite electrolyte membrane of the present invention has unique interface regulation capabilities, good interface stability, and long cycle life. The organic cage cation framework of the present invention can form a stable interaction with the lithium metal surface, inducing the formation of a uniform and dense solid electrolyte interface (SEI) membrane with low interface impedance and good stability. At the same time, the flexibility of the three-dimensional cross-linked network can adapt to the volume changes during the lithium metal deposition / stripping process, maintain the tightness of the interface contact, and avoid interface desorption.

[0077] (6) The composite electrolyte membrane of the present invention has excellent safety performance and is inherently safe with no leakage. The electrolyte membrane of the present invention has good flame retardancy and does not burn when in contact with open flame, solving the flammability problem of traditional liquid electrolytes; at the same time, it has excellent flexibility and can withstand mechanical damage such as folding and cutting, making it suitable for the preparation of flexible batteries. The all-solid-state structure completely eliminates the safety hazards of liquid electrolyte leakage, and the inherent safety is greatly improved.

[0078] (7) The preparation process of the composite electrolyte membrane of the present invention is simple and controllable, and is suitable for large-scale industrial production. The present invention preferably adopts a solvent-free in-situ photocuring process, which avoids the large-scale use and residue of organic solvents, and is environmentally friendly; moreover, the spinning and curing processes can be carried out continuously, with high production efficiency, and is suitable for large-scale industrial production.

[0079] This invention pioneers an organic cage ion conductor-enhanced composite electrolyte system at the material system level, and combines electrospinning and in-situ photocuring processes to construct a three-dimensional cross-linked nanofiber network, achieving synergistic enhancement of ion conduction and mechanical strength. This represents a dual-architectural innovation in both material system and preparation process, rather than simply parameter optimization. Attached Figure Description

[0080] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0081] Figure 1 This is a schematic diagram of the preparation process of the composite electrolyte membrane in Embodiment 1 of the present invention.

[0082] Figure 2 This is a schematic diagram of the three-dimensional network structure of the composite electrolyte membrane in Embodiment 1 of the present invention.

[0083] Figure 3 This is a schematic diagram of the molecular structure and synthesis route of the organic cage ion conductor in Example 1 of the present invention.

[0084] Figure 4 This is a schematic diagram of the interface structure between the composite electrolyte membrane and lithium metal in Embodiment 6 of the present invention.

[0085] Figure 5 This is a schematic diagram of the all-solid-state lithium metal battery structure in Embodiment 6 of the present invention. Detailed Implementation

[0086] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention. The processes, conditions, reagents, experimental methods, etc., for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and general knowledge in the art, and the present invention does not have any special limitations.

[0087] Example 1:

[0088] This embodiment provides an organic cage-reinforced electrospun composite electrolyte membrane and its preparation method, such as... Figure 1 As shown, its preparation method is as follows:

[0089] (1) The polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight Mn=400000), and the crosslinking agent is polyethylene glycol diacrylate (PEGDA, molecular weight Mn= Lithium perchlorate (1000 g / mol) and organic cage ion conductor lithium-cage ion conductor-lithium perchlorate (vacuum dried at 80℃ for 12 h) were mixed at a mass ratio of 6:2.5:1.5, at which point the organic cage ion conductor accounted for 15 wt% of the total polymer mass. The mixture was added to a DMF / acetone (1:1) mixed solvent and stirred at room temperature for 6 h until completely dissolved to form a transparent solution. Then, lithium bis(2,4,6-trimethylbenzoyl)phosphine oxide (LiTFSI, vacuum dried at 100℃ for 12 h) (20 wt% of the total monomer mass) and phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (0.5 wt% of the total monomer mass) were added and stirred for another 2 h to obtain a uniform and transparent spinning precursor solution. The entire preparation process was carried out in an argon-filled glove box, and the water and oxygen content was below 0.1 ppm.

[0090] like Figure 3 As shown, the preparation method of the organic cage ion conductor lithium-cage-based ion conductor lithium perchlorate in this embodiment is as follows:

[0091] Step 1: Synthesis of imine cage (CC1)

[0092] Equimolar amounts of 1,3,5-tricarboxymethyl phloroglucinol and ethylenediamine were weighed and dissolved in methanol. The mixture was stirred at room temperature for 24 h under the protection of inert argon gas. The precipitate formed by the reaction was collected by filtration, washed with methanol as a cold solvent to remove unreacted monomers, and dried to obtain the intermediate imine cage CC1.

[0093] Step 2: Preparation of amine cage (RCC1) by reduction

[0094] The dried CCC1 was suspended in tetrahydrofuran; excess sodium borohydride was added in batches under ice bath cooling; after the addition was complete, the temperature was restored to room temperature and the reaction was stirred for 12 h until the imine bonds were completely reduced to amine bonds; after the reaction was completed, water was carefully added to quench the excess sodium borohydride; the organic solvent was removed by rotary evaporation, the remaining solid was washed with water several times to remove inorganic salts, and after vacuum drying, a white powdery reduced amine cage RCC1 was obtained.

[0095] Step 3: Protonation to prepare chloride salt (RCC1-Cl)

[0096] RCC1 was dispersed in a dilute hydrochloric acid solution. The nitrogen atoms on the amine cage captured protons to form ammonium cations, while simultaneously binding chloride ions as counter anions. After the reaction was complete, the solid product was collected by evaporating the solvent or by precipitation. The product was washed with ethanol to obtain the protonated chloride precursor RCC1-Cl.

[0097] Step 4: Preparation of the final product (RCC1-LiClO4) using lithium salt composites.

[0098] RCC1-Cl was dispersed in a 15wt% lithium perchlorate-ethyl acetate solution and subjected to ion exchange at 50°C. The solution was changed every 48 hours for a total of 3 times. Centrifugation was used to separate the porous organic cage molecular framework and the compound formed by the combination of perchlorate ions. After washing, the compound was mixed with lithium perchlorate in an ethanol-water solvent. After removing the solvent, the compound was dried under vacuum at 80°C overnight to obtain the organic cage-based lithium-ion conductor lithium-cage-based ion conductor lithium perchlorate.

[0099] (2) The spinning precursor solution was loaded into a syringe and high-speed electrospinning was performed using a high-speed rotating roller as a collector to collect the precursor fiber membrane. The parameters of high-speed electrospinning were: flow rate 1.0 mL / h, positive voltage 17 kV, negative voltage -3 kV, collecting roller speed 3000 rpm, temperature 25℃, and humidity <30%.

[0100] (3) The precursor fiber membrane was cured by irradiating it with a 30W, 365nm wavelength ultraviolet light for 5 minutes to allow the crosslinking agent to undergo a polymerization reaction and form a crosslinked three-dimensional nanofiber network structure (e.g. Figure 2 As shown in the figure, a composite electrolyte membrane is obtained.

[0101] The performance of the composite electrolyte membrane prepared in this embodiment was tested, and the results are as follows:

[0102] Electrolyte membrane thickness: 15 μm;

[0103] Room temperature ionic conductivity: 2.5 × 10⁻⁶ -4 S / cm;

[0104] Lithium transference number: 0.65;

[0105] Electrochemical window: 5.6V;

[0106] Tensile strength: 12.5 MPa.

[0107] Example 2:

[0108] This embodiment provides an organic cage-reinforced electrospun composite electrolyte membrane and its preparation method, which is as follows:

[0109] (1) The polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight Mn=400000), and the crosslinking agent is polyethylene glycol diacrylate (PEGDA, molecular weight Mn= Lithium perchlorate (1000 g / mol) and organic cage ion conductor lithium-cage-based ion conductor lithium perchlorate (preparation method as in Example 1, vacuum dried at 80℃ for 12 h) were mixed at a mass ratio of 6.5:2.5:1, at which point the organic cage ion conductor accounted for 10 wt% of the total polymer mass. The mixture was added to a DMF / acetone (1:1) mixed solvent and stirred at room temperature for 6 h until completely dissolved to form a transparent solution. Then, lithium salt bis(2,4,6-trimethylbenzoyl)phosphine oxide (LiTFSI, vacuum dried at 100℃ for 12 h) accounting for 20 wt% of the total monomer mass and photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide accounting for 0.5 wt% of the total monomer mass were added and stirred for another 2 h to obtain a uniform and transparent spinning precursor solution. The entire preparation process was carried out in an argon-filled glove box, and the water and oxygen content was below 0.1 ppm.

[0110] (2) The spinning precursor solution was loaded into a syringe and high-speed electrospinning was performed using a high-speed rotating roller as a collector to collect the precursor fiber membrane. The parameters of high-speed electrospinning were: flow rate 1.0 mL / h, positive voltage 17 kV, negative voltage -3 kV, collecting roller speed 3000 rpm, temperature 25℃, and humidity <30%.

[0111] (3) The precursor fiber membrane was cured by irradiating it with a 30W, 365nm wavelength ultraviolet light for 5 minutes, so that the crosslinking agent underwent a polymerization reaction to form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

[0112] The performance of the composite electrolyte membrane prepared in this embodiment was tested, and the results are as follows:

[0113] Electrolyte membrane thickness: 15 μm;

[0114] Room temperature ionic conductivity: 1.8 × 10⁻⁶ -4 S / cm;

[0115] Lithium transference number: 0.58;

[0116] Electrochemical window: 5.4V;

[0117] Tensile strength: 13.8 MPa.

[0118] Example 3:

[0119] This embodiment provides an organic cage-reinforced electrospun composite electrolyte membrane and its preparation method, which is as follows:

[0120] (1) The polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight Mn=400000), and the crosslinking agent is polyethylene glycol diacrylate (PEGDA, molecular weight Mn= Lithium perchlorate (1000 g / mol) and organic cage ion conductor lithium-cage-based ion conductor lithium perchlorate (preparation method as in Example 1, vacuum dried at 80℃ for 12 h) were mixed at a mass ratio of 6:2:2, at which point the organic cage ion conductor accounted for 20 wt% of the total polymer mass. The mixture was added to a DMF / acetone (1:1) mixed solvent and stirred at room temperature for 6 h until completely dissolved to form a transparent solution. Then, lithium salt bis(2,4,6-trimethylbenzoyl)phosphine oxide (LiTFSI, vacuum dried at 100℃ for 12 h) accounting for 20 wt% of the total monomer mass and photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide accounting for 0.5 wt% of the total monomer mass were added and stirred for another 2 h to obtain a uniform and transparent spinning precursor solution. The entire preparation process was carried out in an argon-filled glove box, and the water and oxygen content was below 0.1 ppm.

[0121] (2) The spinning precursor solution was loaded into a syringe and high-speed electrospinning was performed using a high-speed rotating roller as a collector to collect the precursor fiber membrane. The parameters of high-speed electrospinning were: flow rate 1.0 mL / h, positive voltage 17 kV, negative voltage -3 kV, collecting roller speed 3000 rpm, temperature 25℃, and humidity <30%.

[0122] (3) The precursor fiber membrane was cured by irradiating it with a 30W, 365nm wavelength ultraviolet light for 5 minutes, so that the crosslinking agent underwent a polymerization reaction to form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

[0123] The performance of the composite electrolyte membrane prepared in this embodiment was tested, and the results are as follows:

[0124] Electrolyte membrane thickness: 16 μm;

[0125] Room temperature ionic conductivity: 3.2 × 10⁻⁶ -4 S / cm;

[0126] Lithium transference number: 0.70;

[0127] Electrochemical window: 5.7V;

[0128] Tensile strength: 10.2 MPa.

[0129] Example 4:

[0130] This embodiment provides an organic cage-reinforced electrospun composite electrolyte membrane and its preparation method, which is as follows:

[0131] (1) The polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight Mn=400000), and the crosslinking agent is polyethylene glycol diacrylate (PEGDA, molecular weight Mn= Lithium perchlorate (1000 g / mol) and organic cage ion conductor lithium-cage-based ion conductor lithium perchlorate (preparation method as in Example 1, vacuum dried at 80℃ for 12 h) were mixed at a mass ratio of 6:2.5:1.5, at which point the organic cage ion conductor accounted for 15 wt% of the total polymer mass. The mixture was added to a DMF / acetone (1:1) mixed solvent and stirred at room temperature for 6 h until completely dissolved to form a transparent solution. Then, lithium salt bis(2,4,6-trimethylbenzoyl)phosphine oxide (LiTFSI, vacuum dried at 100℃ for 12 h) accounting for 20 wt% of the total monomer mass and photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide accounting for 0.5 wt% of the total monomer mass were added and stirred for another 2 h to obtain a uniform and transparent spinning precursor solution. The entire preparation process was carried out in an argon-filled glove box, and the water and oxygen content was below 0.1 ppm.

[0132] (2) The spinning precursor solution was loaded into a syringe, and high-speed electrospinning was performed using a high-speed rotating roller as a collector to collect the precursor fiber membrane. The parameters for high-speed electrospinning were: flow rate 1.0 mL / h, positive voltage 17 kV, negative voltage -3 kV, collecting roller speed 3000 rpm, temperature 25℃, and humidity <30%. By shortening the spinning time, the thickness of the electrolyte membrane can be precisely controlled to achieve the preparation of an ultrathin electrolyte membrane.

[0133] (3) The precursor fiber membrane was cured by irradiating it with a 30W, 365nm wavelength ultraviolet light for 5 minutes, so that the crosslinking agent underwent a polymerization reaction to form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

[0134] The performance of the composite electrolyte membrane prepared in this embodiment was tested, and the results are as follows:

[0135] Electrolyte membrane thickness: 12 μm;

[0136] Room temperature ionic conductivity: 2.5 × 10⁻⁶ -4 S / cm;

[0137] Lithium transference number: 0.65;

[0138] Electrochemical window: 5.6V;

[0139] Tensile strength: 9.8 MPa.

[0140] Example 5:

[0141] This embodiment provides an organic cage-reinforced electrospun composite electrolyte membrane and its preparation method, which is as follows:

[0142] (1) The polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP, molecular weight Mn=400000), and the crosslinking agent is polyethylene glycol diacrylate (PEGDA, molecular weight Mn= Lithium perchlorate (1000 g / mol) and organic cage ion conductor lithium-cage-based ion conductor lithium perchlorate (preparation method as in Example 1, vacuum dried at 80℃ for 12 h) were mixed at a mass ratio of 7:2:1, at which point the organic cage ion conductor accounted for 10 wt% of the total polymer mass. The mixture was added to a DMF / acetone (1:1) mixed solvent and stirred at room temperature for 6 h until completely dissolved to form a transparent solution. Then, lithium bis(2,4,6-trimethylbenzoyl)phosphine oxide (LiTFSI, vacuum dried at 100℃ for 12 h) accounting for 20 wt% of the total monomer mass and photoinitiator phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (0.5 wt% of the total monomer mass) were added and stirred for another 2 h to obtain a uniform and transparent spinning precursor solution. The entire preparation process was carried out in an argon-filled glove box, and the water and oxygen content was below 0.1 ppm.

[0143] (2) The spinning precursor solution was loaded into a syringe and high-speed electrospinning was performed using a high-speed rotating roller as a collector to collect the precursor fiber membrane. The parameters of high-speed electrospinning were: flow rate 1.0 mL / h, positive voltage 17 kV, negative voltage -3 kV, collecting roller speed 3000 rpm, temperature 25℃, and humidity <30%.

[0144] (3) The precursor fiber membrane was cured by irradiating it with a 30W, 365nm wavelength ultraviolet light for 5 minutes, so that the crosslinking agent underwent a polymerization reaction to form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

[0145] The performance of the composite electrolyte membrane prepared in this embodiment was tested, and the results are as follows:

[0146] Electrolyte membrane thickness: 15 μm;

[0147] Room temperature ionic conductivity: 2.1 × 10⁻⁶ -4 S / cm;

[0148] Lithium transference number: 0.62;

[0149] Electrochemical window: 5.5V;

[0150] Tensile strength: 14.2 MPa.

[0151] Example 6:

[0152] This embodiment provides an application of an organic cage-reinforced electrospun composite electrolyte membrane in an all-solid-state lithium metal battery, such as... Figure 4 and Figure 5 As shown, the all-solid-state lithium metal battery is configured as follows:

[0153] Positive electrode: NCM811, areal density 30 mg / cm³ 2 ;

[0154] Electrolyte: The composite electrolyte membrane prepared in Example 1;

[0155] Negative electrode: Lithium metal foil, 50μm thick;

[0156] Test conditions:

[0157] Test temperature: 45℃;

[0158] Voltage range: 2.8-4.4V;

[0159] Charge / discharge rate: 0.33C / 0.33C;

[0160] Test results:

[0161] First-cycle discharge capacity: 195mAh / g;

[0162] First-lap efficiency: 89.5%;

[0163] Capacity retention after 100 cycles: 92.3%;

[0164] 0.5C rate capacity retention: 88%;

[0165] 1C rate capacity retention: 78%.

[0166] Comparative Example 1:

[0167] It uses a traditional PEO-based solid electrolyte, without adding an organic cage, and does not employ electrospinning technology.

[0168] Ingredients and formula:

[0169] PEO:LiTFSI = 8:1 (EO:Li = 16:1);

[0170] It contains no organic cages and no cross-linking agents.

[0171] Preparation process:

[0172] Solution casting method, using acetonitrile solvent, drying at 60℃ for 24 hours.

[0173] Performance testing:

[0174] Electrolyte membrane thickness: 80 μm;

[0175] Room temperature ionic conductivity: 5.2 × 10⁻⁶ -6 S / cm;

[0176] Lithium transference number: 0.18;

[0177] Electrochemical window: 4.4V;

[0178] Tensile strength: 3.5 MPa.

[0179] The conventional PEO-based solid electrolyte of Comparative Example 1 was assembled into an all-solid-state lithium metal battery according to the method of Example 6.

[0180] Comparative Example 2:

[0181] The PVDF-HFP skeleton is electrospun and impregnated with PEO electrolyte, without the addition of organic cages.

[0182] Ingredients and formula:

[0183] Electrospun PVDF-HFP fiber membrane;

[0184] Impregnated with PEO-LiTFSI electrolyte.

[0185] Preparation process:

[0186] PVDF-HFP fiber membranes were prepared by electrospinning.

[0187] Impregnate with PEO-LiTFSI / acetonitrile solution and dry.

[0188] Performance testing:

[0189] Electrolyte membrane thickness: 45 μm;

[0190] Room temperature ionic conductivity: 2.8 × 10⁻⁶ -5 S / cm;

[0191] Lithium transference number: 0.22;

[0192] Electrochemical window: 4.6V;

[0193] Tensile strength: 6.8 MPa.

[0194] Comparative Example 3:

[0195] Add an organic cage, but do not perform cross-linking and curing, and do not use electrospinning:

[0196] Ingredients and formula:

[0197] PVDF-HFP: Organic cage (lithium-cage-based ionic conductor-lithium perchlorate) = 85:15;

[0198] LiTFSI 20wt%

[0199] No cross-linking agent, no light curing.

[0200] Preparation process:

[0201] Solution casting method, DMF solvent, dried at 80℃ for 24 hours.

[0202] Performance testing:

[0203] Electrolyte membrane thickness: 65 μm;

[0204] Room temperature ionic conductivity: 8.5 × 10⁻⁶ -5 S / cm;

[0205] Lithium transference number: 0.55;

[0206] Electrochemical window: 5.2V;

[0207] Tensile strength: 4.2 MPa.

[0208] Comparative Example 4:

[0209] Electrospinning is used, but in-situ photocuring and crosslinking are not performed:

[0210] Ingredients and formula:

[0211] Same as Example 1, but without adding a photoinitiator and without photocuring.

[0212] Preparation process:

[0213] Electrospinning is the same as in Example 1;

[0214] No UV curing is performed.

[0215] Performance testing:

[0216] Electrolyte membrane thickness: 15 μm;

[0217] Room temperature ionic conductivity: 2.3 × 10⁻⁶ -4 S / cm;

[0218] Lithium transference number: 0.63;

[0219] Electrochemical window: 5.5V;

[0220] Tensile strength: 5.8 MPa.

[0221] The composite electrolyte membranes prepared in Examples 1-6 and Comparative Examples 1-4 were subjected to performance tests, and the test methods are as follows:

[0222] (1) Thickness measurement: The thickness of the electrolyte membrane at different locations was measured using a high-precision micrometer, and the average value was taken.

[0223] (2) Ionic conductivity test: The electrochemical impedance spectroscopy (EIS) method was used, with the electrolyte membrane sandwiched between two stainless steel blocking electrodes, at a frequency range of 10. 6 Hz~10 -2 Hz, AC amplitude 5mV, calculate ionic conductivity based on bulk resistance of impedance spectrum.

[0224] (3) Lithium transference number test: The constant potential polarization method combined with the AC impedance method is used. The electrolyte membrane is sandwiched between two lithium metal electrodes, a polarization voltage of 10mV is applied, the steady-state current is recorded, and the lithium transference number is calculated by combining the interface impedance before and after polarization.

[0225] (4) Electrochemical window test: Linear sweep voltammetry (LSV) was used, with lithium metal as the counter electrode and reference electrode, and stainless steel as the working electrode. The scan rate was 1 mV / s, scanning from the open circuit voltage to 6.0 V, with a current density of 0.1 mA / cm². 2 The voltage at that time is used as the electrochemical oxidation window.

[0226] (5) Mechanical property test: Tensile test was conducted using a universal testing machine with a sample size of 10mm × 50mm and a tensile rate of 5mm / min. The tensile strength and elongation at break were tested.

[0227] (6) Lithium symmetric battery cycle test: The electrolyte membrane is sandwiched between two lithium metal sheets to assemble a CR2032 coin cell. The test is performed at 0.1 mA / cm². 2 Constant current charge and discharge were performed at the current density, with each charge and discharge cycle lasting 1 hour, and the stable cycle time was tested.

[0228] (7) Full cell performance test: The Blue Electric test system is used to test the first-cycle coulombic efficiency, cycle performance and rate performance of the battery.

[0229] The test results are shown in Tables 1 and 2 below.

[0230] Table 1. Performance test results of each embodiment and comparative example

[0231] Example 1 15 <![CDATA[2.5×10 -4 ]]> 0.65 5.6 12.5 >5000 Example 2 15 <![CDATA[1.8×10 -4 ]]> 0.58 5.4 13.8 >4500 Example 3 16 <![CDATA[3.2×10 -4 ]]> 0.70 5.7 10.2 >3500 Example 4 12 <![CDATA[2.5×10 -4 ]]> 0.65 5.6 9.8 >3000 Example 5 15 <![CDATA[2.1×10 -4 ]]> 0.62 5.5 14.2 >4800 Comparative Example 1 80 <![CDATA[5.2×10 -6 ]]> 0.18 4.4 3.5 <500 Comparative Example 2 45 <![CDATA[2.8×10 -5 ]]> 0.22 4.6 6.8 <1000 Comparative Example 3 65 <![CDATA[8.5×10 -5 ]]> 0.55 5.2 4.2 <800 Comparative Example 4 15 <![CDATA[2.3×10 -4 ]]> 0.63 5.5 5.8 <1500

[0232] Table 2. Full battery performance test results (Comparison of assembled batteries in Example 6 and Comparative Example 1)

[0233] Example 6 195 89.5% 92.3% 88% 78% Comparative Example 1 Battery 182 85.2% 78.5% 65% 45%

[0234] The analysis results are shown below:

[0235] (1) Ionic conductivity analysis: The room temperature ionic conductivity of all examples reached 10. -4 The conductivity was on the order of S / cm, nearly 50 times higher than the traditional PEO electrolyte in Comparative Example 1, and nearly 10 times higher than the electrospinning impregnation system in Comparative Example 2. This fully demonstrates the significant enhancing effect of organic cage ionic conductors on ion conduction. Example 3 had the highest organic cage content and also the highest conductivity, indicating that increasing the organic cage content within a certain range can continuously improve ionic conductivity.

[0236] (2) Lithium transference number analysis: The lithium transference numbers of all examples were above 0.58, with Example 1 reaching 0.65 and Example 3 reaching 0.70, which is more than 3 times that of traditional PEO electrolytes. High lithium transference numbers can significantly reduce concentration polarization and improve rate performance. The anchoring of anions by the cation framework of the organic cage is the key mechanism for improving lithium transference numbers.

[0237] (3) Electrochemical window analysis: The electrochemical windows of all examples are above 5.4V, with Example 1 reaching 5.6V, which is much higher than the 4.4V of the traditional PEO electrolyte, and can be matched with high-voltage cathode materials of 4.4V and 4.5V. The synergistic effect of the organic cage and PVDF-HFP is the reason for the high voltage stability.

[0238] (4) Mechanical strength analysis: The tensile strength of Example 1 reached 12.5 MPa, which is 3.5 times that of Comparative Example 1 and more than 2 times that of Comparative Example 4 (without crosslinking). This indicates that the three-dimensional network structure formed by in-situ photocuring crosslinking is crucial to the improvement of mechanical strength. The strength of Examples 2 and 5 is even higher because the content of organic cages is lower or the proportion of PVDF-HFP is higher, and the contribution of the polymer matrix is ​​greater.

[0239] (5) Analysis of lithium dendrite suppression capability: The lithium symmetric battery of Example 1 can cycle stably for more than 5000 hours, which is more than 10 times that of Comparative Example 1, fully demonstrating the excellent lithium dendrite suppression capability of the present invention. The synergistic effect of high-strength three-dimensional cross-linked network and high lithium migration number is the key to lithium dendrite suppression.

[0240] (6) Full cell performance analysis: The full cell of Example 6 achieved an initial efficiency of 89.5%, a capacity retention rate of 92.3% after 100 cycles, and a 1C rate capacity retention rate of 78%, all of which were significantly better than the battery of Comparative Example 1. High ion conductivity, high lithium transference number, and stable interface are the main reasons for the improved full cell performance.

[0241] In summary, this invention achieves a comprehensive breakthrough in ionic conductivity, lithium transference number, electrochemical window, mechanical strength, and lithium dendrite suppression through the synergistic effect of organic cage ion conductor enhancement and electrospinning three-dimensional cross-linked network. Its performance far exceeds the level of existing technologies and has extremely high industrial application value.

[0242] Specific embodiments have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only for the purpose of helping to understand the method and core ideas of this invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this invention. Therefore, the content of this specification should not be construed as a limitation of this invention.

Claims

1. A method for preparing an organic cage-reinforced electrospun composite electrolyte membrane, characterized in that, The preparation method includes the following steps: Step 1: Mix the polymer matrix, crosslinking agent and organic cage ionic conductor, add to the mixed solvent and stir until a transparent solution is formed, then add lithium salt and initiator, and continue stirring to obtain a uniform and transparent spinning precursor solution; Step 2: The spinning precursor solution is subjected to high-speed electrospinning to collect the precursor fiber membrane. Step 3: The precursor fiber membrane is cured to allow the crosslinking agent to polymerize and form a crosslinked three-dimensional nanofiber network structure, thus obtaining a composite electrolyte membrane.

2. The method according to claim 1, characterized in that, In step one, the polymer matrix is ​​selected from one or more combinations of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), and polyethylene oxide (PEO); Preferably, the polymer matrix is ​​polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) with a molecular weight Mn=400000.

3. The method according to claim 1, characterized in that: In step one, the crosslinking agent is selected from one or more combinations of polyethylene glycol diacrylate (PEGDA), trimethylolpropane triacrylate (TMPTA), ethoxylated trimethylolpropane triacrylate (EO-TMPTA), and pentaerythritol tetraacrylate (PETA); Preferably, the crosslinking agent is polyethylene glycol diacrylate (PEGDA) with a molecular weight Mn = 1000 g / mol.

4. The method according to claim 1, characterized in that, In step one, the organic cage ion conductor is selected from one or more combinations of lithium-cage-based ion conductors—lithium perchlorate, imine cages, borate ester cages, and covalent organic framework (COF) molecular cages; Preferably, the organic cage ion conductor is a lithium-cage-based ion conductor-lithium perchlorate, which is used after being vacuum dried at 80°C for 12 hours.

5. The method according to any one of claims 1 to 4, characterized in that: In step one, the mass ratio of the polymer matrix, the crosslinking agent, and the organic cage ion conductor is (5~7):(2~3):(1~2). Preferably, the mass ratio of the polymer matrix, the crosslinking agent, and the organic cage ionic conductor is (5.5~6.5):(2~2.5):1.5; More preferably, the mass ratio of the polymer matrix, the crosslinking agent, and the organic cage ionic conductor is 6:2.5:1.

5.

6. The method according to claim 1, characterized in that, In step one, the mixed solvent is a mixture of N,N-dimethylformamide and acetone in a volume ratio of 1:1; Preferably, after adding the mixed solvent, the mixture is stirred at room temperature for 6 hours.

7. The method according to claim 1, characterized in that, In step one, the lithium salt is selected from one or more combinations of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4); Preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), which is used after being vacuum dried at 100°C for 12 hours; Preferably, the amount of lithium salt added is 18wt% to 22wt% of the total mass of the polymer matrix, crosslinking agent, and organic cage ionic conductor; More preferably, the amount of lithium salt added is 20 wt% of the total mass of the polymer matrix, crosslinking agent and organic cage ionic conductor.

8. The method according to claim 1, characterized in that, In step one, depending on the curing method in step three, the initiator is selected from photoinitiators or thermal initiators; Preferably, the photoinitiator is selected from phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; Preferably, the thermal initiator is selected from azobisisobutyronitrile; Preferably, the amount of the initiator added is 0.5% of the total mass of the polymer matrix, crosslinking agent, and organic cage ionic conductor.

9. The method according to claim 1, characterized in that, In step two, the parameters of the high-speed electrospinning are: injection flow rate 0.8~1.2mL / h, spinning positive voltage 15~20kV, negative voltage -2~-4kV, and collecting roller speed 2500~3500rpm; Preferably, the parameters of the high-speed electrospinning are: injection flow rate 1 mL / h, spinning positive voltage 17 kV, negative voltage -3 kV, and collecting roller speed 3000 rpm.

10. The method according to claim 1, characterized in that, In step three, the curing process is selected from photocuring or thermocuring; Preferably, the photocuring conditions are: curing is performed by irradiation with a 30W, 365nm wavelength ultraviolet lamp, and the curing time is 4~6 minutes, preferably 5 minutes; Preferably, the thermosetting conditions are: heating and curing at 60~80℃ for 2~4 hours.

11. An organic cage-reinforced electrospun composite electrolyte membrane, which is prepared by the method described in any one of claims 1 to 10.

12. The organic cage-reinforced electrospun composite electrolyte membrane according to claim 11, characterized in that: The composite electrolyte membrane has a three-dimensional cross-linked nanofiber network structure; its thickness is 12~20μm, preferably 15~18μm; its tensile strength reaches 9.8MPa~14.2MPa; and its room temperature ionic conductivity is 1.8×10⁻⁶. -4 S / cm ~ 3.2 × 10 -4 S / cm; lithium transference number is 0.58~0.7; electrochemical window is 5.4V~5.7V.

13. The application of the organic cage-reinforced electrospun composite electrolyte membrane obtained by the method of any one of claims 1 to 10, or the organic cage-reinforced electrospun composite electrolyte membrane of claim 11 or 12, in the preparation of all-solid-state lithium metal batteries.

14. An all-solid-state lithium metal battery, characterized in that: The electrolyte membrane used to prepare the all-solid-state lithium metal battery is an organic cage-reinforced electrospun composite electrolyte membrane obtained by the method described in any one of claims 1 to 10, or an organic cage-reinforced electrospun composite electrolyte membrane described in claim 11 or 12.

Citation Information

Patent Citations

  • All-solid-state secondary battery and method for manufacturing the same

    CN111146492B

  • A method for preparing an ultrathin continuous network structure composite electrolyte membrane

    CN116864801B

  • Polymer solid electrolyte membrane and preparation method thereof, solid-state battery, battery pack and electric equipment

    CN121862833A

  • Solid-state battery monomer, composite electrolyte material, battery device and electric device

    CN122246216A